Mapping Analysis of the Research Trends on Digital Technologies and Circular Economy in Tourism - NASSANBEKOVA, Samalgul; YESHENKULOVA, Gaukhar (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).24, 2022)
Tourism as an industry, which is interdependent and influences several sectors of the economy, has the potential significantly to enhance global sustainability. One of the new paradigm of sustainable development is a circular economy. Circular economy principles include repurposing business for the benefit of society and the environment, replacing materials with renewable and natural resources, producing value from "waste," and using energy and resources efficiently. Digital technologies are considered as a catalyst and important supporter of movement to circularity. To find relationship between digital technologies and circular tourism a bibliometric analysis of scientific literature has been conducted in this study. For counting and visualization the authors, keywords and text in the abstracts co-occurrence we have used VOSviewer software. The findings shown tight links in the studies between two concepts and how they are interrelated. In this study, we defined the term “circular economy”, the most perspective digital solutions for creation circular tourism, and aspects pertaining to social effect, institutional reforms, and defining the role of the non-profit sector should not be disregarded in the development of circular tourism. In the drawn conclusion stated, that more empirical investigations are required to collaborate theories, models, and frameworks that have been produced, since the majority of studies are grounded in theory.